IgG from patients with pulmonary arterial hypertension and/or systemic sclerosis binds to vascular smooth muscle cells and induces cell contraction. Issue 4 (14th November 2011) - Bussone, Guillaume; Tamby, Mathieu C; Calzas, Cynthia; Kherbeck, Nada; Sahbatou, Younes; Sanson, Claire; Ghazal, Khaldoun; Dib, Hanadi; Weksler, Babette B; Broussard, Cédric; Verrecchia, Franck; Yaici, Azzedine; et al.
Abstract : Objectives: Pulmonary arterial hypertension (PAH) is characterised by remodelling of pulmonary arteries with enhanced vascular smooth muscle cell (VSMC) contraction, migration and proliferation. The authors investigated the presence of antibodies to human VSMCs in the serum of patients with systemic sclerosis with or without PAH and idiopathic PAH (iPAH). Methods and results: Antibodies to VSMCs were detected by immunofluorescence in sera from healthy controls and patients with scleroderma without PAH, scleroderma-associated PAH and iPAH. Serum IgG from these patients induced contraction of VSMCs in a collagen matrix in contrast with IgG from healthy controls. Several protein spots of interest and target antigens were identified by two-dimensional immunoblotting and MS, including stress-induced phosphoprotein 1 and α-enolase. Finally, antibodies to stress-induced phosphoprotein 1 were detected by ELISA in sera from 84%, 76% and 24% of patients with scleroderma without PAH, scleroderma-associated PAH and iPAH, respectively, compared with only 3% of healthy controls. Conclusion: The authors have identified IgG that binds to VSMCs in the serum of patients with scleroderma and iPAH. These antibodies may be pathogenic by modulating vascular contraction. The target antigens of these antibodies are stress-induced phosphoprotein 1 and α-enolase.